2019
DOI: 10.3390/nu11061230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1 Year Krill Oil Supplementation on Cognitive Achievement of Dutch Adolescents: A Double-Blind Randomized Controlled Trial

Abstract: Long-chain polyunsaturated fatty acids (LCPUFA) are important for brain development and function, maybe especially during adolescence. Observational studies have demonstrated an association between fish consumption (a source of LCPUFA) and cognition in adolescents, but intervention trials are lacking. The goal of the current study was to investigate the effect of one year of krill oil (a source of LCPUFA) supplementation on the cognitive performance of adolescents with a low Omega-3 Index (O3I ≤ 5%). A double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…It might not be surprising that the change scores did not differ when we consider that there was a clear overlap in DHA blood values between the placebo group and the active group. A similar problem arose in the study of van der Wurff et al, a similar Omega-3 index post-intervention was measured in the placebo and the active group due to non-adherence to the study protocol, which could explain the result of similar cognitive test results in both groups [ 47 ].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…It might not be surprising that the change scores did not differ when we consider that there was a clear overlap in DHA blood values between the placebo group and the active group. A similar problem arose in the study of van der Wurff et al, a similar Omega-3 index post-intervention was measured in the placebo and the active group due to non-adherence to the study protocol, which could explain the result of similar cognitive test results in both groups [ 47 ].…”
Section: Discussionmentioning
confidence: 89%
“…Of the 33 studies included in this review, 13 studies had no reported blood fatty acid concentrations [ 29 , 31 , 33 , 35 , 36 , 38 , 43 , 44 , 45 , 49 , 52 , 53 , 55 ]. In 20 studies, fatty acid concentrations were reported, and the fatty acid concentrations were analyzed in a variety of bodily tissues and blood fractions (note that in some studies multiple fractions were utilized): plasma fatty acids [ 27 , 32 , 33 , 56 ], phospholipids in erythrocyte membranes [ 28 , 41 ], plasma phosphatidylcholine [ 30 ], erythrocyte phosphatidylcholine [ 30 ], erythrocyte phosphatidylethanolamine [ 30 ], cheek cells [ 37 , 48 ], capillary whole blood [ 40 , 46 , 47 , 50 ], serum phospholipids [ 42 , 57 , 58 ], total fatty acids in erythrocyte membrane [ 39 , 56 , 59 ], glycerol-phospholipids in plasma [ 51 ] and erythrocytes [ 54 ]. Unfortunately, recalculation formulae to the O3I equivalence are only available for a limited number of blood fractions [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perinatal mortality was not significantly reduced (RR 0.75, 95% CI 0.54 to 1.03). Pre-eclampsia might have been reduced (RR 0.84, 95% CI 0.69 to 1.01), corresponding to epidemiologic data [42][43][44]. An improvement of postnatal depression was not found, nor were parameters of cognition improved in the child.…”
Section: Clinical Benefit Of Omega-3s In Pregnancymentioning
confidence: 92%